Preliminary Phytochemical Screening and Quantitative Analysis of Total Flavonoid and Phenolic Content of Some Medicinal Plants Found In Nepal - Shukla, Ambar (Scientific Researches in Academia, 2023)
A. vulgaris L. (common Mugwort), Nyctanthes arbor-tristis, Utrica diociea also called Titepati, Parijata and Sisno respectively in Nepali, are the species with great importance in the history of medicine and were called the “mother of herbs” in the middle ages. All of them were common herbaceous plants that exhibit high morphological and phytochemical variability depending on the location where they occur. The main objective of this research paper was to identify the different phytochemical constituents qualitatively and quantitatively. The aerial parts of the plants were shaded dried, grinded and soaked in the methanol solvent to prepare the extract. The extracts were, then, examined for the qualitative tests. Different phytochemical constituents (Flavonoids, Phenols, Alkaloids, Steroids, Tannins, Terpenoids, Coumarins, Quinones, and Glycosides) were identified from the methanolic extract of the leaves of plant. Similarly, quantitatively Total Flavonoid Content (TFC) and Total Phenolic Content (TPC) were calculated by using UV/Vis Spectrophotometer. As a result, this study highly supported the medicinal use of the plant species owing their different phytochemical constituents.